Angle Class II, division 2 malocclusion with pronounced overbite - Locks,Arno (2012)
Angle Class II, division 2, malocclusion is characterized by a Class II molar relation associated with retroclined or vertical positioning of the upper incisors and in general an overbite. This clinical case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as part of the requirements for becoming a BBO Diplomate .